2013
DOI: 10.3109/13880209.2013.805234
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of antimicrobial potential of essential oils ofCinnamomum glanduliferum, Feronia elephantum, Bupleurum hamiltoniiandCyclospermum leptophyllumagainst foodborne pathogens

Abstract: Context: Cinnamomum glanduliferum (Wall.) Meissn. (Lauraceae), Feronia elephantum Correa (Rutaceae), Bupleurum hamiltonii Balak (Apiaceae) and Cyclospermum leptophyllum (Pers.) Sprague ex Britton & P. Wilson (Apiaceae) are common species found in Northwest Himalaya and are widely used as folk medicine. The study became more interesting because hitherto there are no reports on the antimicrobial screening of these species with specific chemical composition.Objective: The antimicrobial potential of the essential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 19 publications
(17 reference statements)
1
9
0
1
Order By: Relevance
“…The results of MIC ( Table ) confirmed the antimicrobial activity of oil quantitatively. The tested oil is highly effective against E. coli with MIC value of 0.49 μg/ml (more than gentamycin in which MIC equaled to 0.98 μg/ml), which agreed with Singh et al . who reported that the extracted essential oil from Indian C. glanduliferum is very active against E. coli ( MIC 3.40 mg/ml).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The results of MIC ( Table ) confirmed the antimicrobial activity of oil quantitatively. The tested oil is highly effective against E. coli with MIC value of 0.49 μg/ml (more than gentamycin in which MIC equaled to 0.98 μg/ml), which agreed with Singh et al . who reported that the extracted essential oil from Indian C. glanduliferum is very active against E. coli ( MIC 3.40 mg/ml).…”
Section: Resultssupporting
confidence: 88%
“…Cinnamon essential oil and its constituents are known to possess various antimicrobial activities. For example, Cinnamomum zeylanicum bark and Cinnamomum glanduliferum leaves exerted antimicrobial activities against both Gram ‐negative and Gram ‐positive bacteria . The other biological activity of cinnamon oil is its anticancer effect.…”
Section: Introductionmentioning
confidence: 99%
“…[106] linalool; a-phellandrene; aterpineol. [104,106] a-terpinene; a-thujene [104,105] Anticancer, [107] antiinflammatory, [105] antimicrobial, [107,108] cytotoxic, [109] gastroprotective, [105] larvicidal [110] Abdominal disorders, [111,112] asthma, [112] bronchitis, [113] cough and cold, [114,115] diabetes, [63] dizziness, [106] dysentery, [114] dyspepsia, [112] gonorrhoea, [111] infestation, [63] head ache, [116] kidney trouble, [63] nausea, [116] oral, [40] pneumonia, [55,113] pyrexia, [55] respiratory problems, [112] rheumatism, [55] shivering, [116] snake bite, [112] tooth ache, [117] wounds [117]…”
Section: Methodsmentioning
confidence: 99%
“…These components are chemically derived from terpenes and their oxygenated derivatives (Solórzano-Santos & Miranda-Novales, 2012). EO possesses many pharmacological effects described, such as antioxidant (Victoria et al, 2012;Wang et al, 2013), antimicrobial (Singh et al, 2013;Stefanakis et al, 2013), and antinociceptive (Amorim et al, 2009).…”
Section: Introductionmentioning
confidence: 99%